2020
DOI: 10.1186/s12301-020-00064-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of microsurgical varicocelectomy in the management of non-obstructive azoospermia with varicocele: our tertiary care centre experience

Abstract: Background Varicocele is an abnormal dilation and tortuosity of the internal spermatic veins within the pampiniform plexus of the spermatic cord. Varicocele is associated with progressive testicular damage and infertility. Azoospermia is associated with a varicocele in approximately 4–14% cases. For men with azoospermia or severe oligoasthenospermia, varicocele repair may result in modest improvement in semen quality which may have a significant advantage on couple’s fertility options. The aim of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Thakur, in his retrospective study in 104 patients on the role of infertility in NOAZ, reported that after varicocelectomy, 18% of them had sperms in their ejaculate. Though 10% of them showed spontaneous pregnancy, fertilization rate was 89% through viable sperms enough for performing assisted ICSI without TESE (21).…”
Section: Urologist's Perspectivesmentioning
confidence: 96%
“…Thakur, in his retrospective study in 104 patients on the role of infertility in NOAZ, reported that after varicocelectomy, 18% of them had sperms in their ejaculate. Though 10% of them showed spontaneous pregnancy, fertilization rate was 89% through viable sperms enough for performing assisted ICSI without TESE (21).…”
Section: Urologist's Perspectivesmentioning
confidence: 96%